2019
DOI: 10.3390/su11247103
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Technological Change under Shared Socioeconomic Pathways and Regional Differences: A Case Study of Irrigation Water Use Efficiency Changes in Chinese Provinces

Abstract: Technological changes in water use efficiency directly influence regional sustainable development. However, few studies have attempted to predict changes in water use efficiency because of the complex influencing factors and regional diversity. The Chinese Government has established a target of 0.6 for the effective utilization coefficient of irrigation water, but it is not clear how the coefficient will change in different provinces in the future. The purpose of this study is to predict irrigation water use e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The Water Futures and Solutions (WFAS) scenario proposed the HE classification method, this method can be combined with the scenario settings of the SSPs to group regions according to their different economic and water resources conditions. The HE classification method uses the calculation results of the research team in this study [21]. According to the HE classification method of the WFAS, the provincial administrative regions of China were classified (excluding the Hong Kong special administrative region, the Macao special administrative region, and the Taiwan region) (Figure 2).…”
Section: The Ssps-he Framework Parameter Setting Methods That Combine...mentioning
confidence: 99%
See 2 more Smart Citations
“…The Water Futures and Solutions (WFAS) scenario proposed the HE classification method, this method can be combined with the scenario settings of the SSPs to group regions according to their different economic and water resources conditions. The HE classification method uses the calculation results of the research team in this study [21]. According to the HE classification method of the WFAS, the provincial administrative regions of China were classified (excluding the Hong Kong special administrative region, the Macao special administrative region, and the Taiwan region) (Figure 2).…”
Section: The Ssps-he Framework Parameter Setting Methods That Combine...mentioning
confidence: 99%
“…It quantitatively describes the five typical developmental pathways of the social economy in the future, and it distinguishes the different emission concentrations caused by the different developmental pathways. In addition, it distinguishes the different climate change responses and adaptabilities formed by the different developmental pathways [21]. The prediction of social and economic scenarios under the different pathways is beneficial for the combination of social and economic development and the natural factor model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the present efficiency of irrigation is low. In China, the mean utilization coefficient of irrigation water was 0.45 in 2019 [3]. Precision irrigation according to soil moisture dynamics is the key to achieving high water use efficiency (WUE, kg m -3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with surface irrigation, drip irrigation can improve irrigation efficiency by 30%, leading to significantly reduced water consumption [9]. Huang et al [10] and Guo et al [11] demonstrated that using watersaving technologies for irrigation could reduce crop water consumption and improve water productivity.…”
Section: Introductionmentioning
confidence: 99%